CREEPAGE OF STEEL CABLES, DAMAGED BY CONTACT AND FRICATIVE CORROSION - Matchenko, Тaras; Radetskaya, Ianina (Proceedings of National Aviation University (archive), 2006)
The mathematical model of creepage determination for steel ropes, taking into account the contact and fricative corrosion, methods of determination of the thermo electro destroying force and electro chemical characteristics, algorithm for determination of the steel cable corrosion speed are considered in the article.